IL-6 Mediates Cross-Talk between Tumor Cells and Activated Fibroblasts in the Tumor Microenvironment - Karakasheva, Tatiana A; Lin, Eric W; Tang, Qiaosi; Qiao, Edmund; Waldron, Todd J; Soni, Monica; Klein-Szanto, Andres J; Sahu, Varun; Basu, Devraj; Ohashi, Shinya; Baba, Kiichiro; Giaccone, Zachary T; et al. (Cancer research (Chicago, Ill.), 2018)
The tumor microenvironment (TME) plays a major role in the pathogenesis of multiple cancer types, including upper-gastrointestinal (GI) cancers that currently lack effective therapeutic options. Cancer-associated fibroblasts (CAF) are an essential component of the TME, contributing to tumorigenesis by secreting growth factors, modifying the extracellular matrix, supporting angiogenesis, and suppressing antitumor immune responses. Through an unbiased approach, we have established that IL-6 mediates cross-talk between tumor cells and CAF not only by supporting tumor cell growth, but also by promoting fibroblast activation. As a result, IL-6 receptor (IL6Rα) and downstream effectors offer opportunities for targeted therapy in upper-GI cancers. IL-6 loss suppressed tumorigenesis in physiologically relevant three-dimensional (3D) organotypic and 3D tumoroid models and murine models of esophageal cancer. Tocilizumab, an anti-IL6Rα antibody, suppressed tumor growth in part via inhibition of STAT3 and MEK/ERK signaling. Analysis of a pan-cancer TCGA dataset revealed an inverse correlation between IL-6 and IL6Rα overexpression and patient survival. Therefore, we expanded evaluation of tocilizumab to head and neck squamous cell carcinoma patient-derived xenografts and gastric adenocarcinoma xenografts, demonstrating suppression of tumor growth and altered STAT3 and ERK1/2 gene signatures. We used small-molecule inhibitors of STAT3 and MEK1/2 signaling to suppress tumorigenesis in the 3D organotypic model of esophageal cancer. We demonstrate that IL6 is a major contributor to the dynamic cross-talk between tumor cells and CAF in the TME. Our findings provide a translational rationale for inhibition of IL6Rα and downstream signaling pathways as a novel targeted therapy in oral-upper-GI cancers. These findings demonstrate the interaction of esophageal cancer and cancer-associated fibroblasts through IL-6 signaling, providing rationale for a novel therapeutic approach to target these cancers. .